Acute care utilisation towards the end of life and the place of death for patients with serious mental disorders: a register-based cohort study in South London. (May 2021) - Wilson, R.; Gaughran, F.; Whitburn, T.; Higginson, I.J.; Gao, W.
Abstract: Objectives: The aim of the study was to explore acute care utilisation towards end of life by and the place of death for patients with serious mental disorders and to demonstrate any inequalities in end-of-life care faced by this patient group. Study design: This is a retrospective cohort study using linked, routinely collected data. Methods: This study used linked data extracted from mental health records, Hospital Episode Statistics and mortality data. Adult cases (≥18 years old) were included if they had a serious mental disorder and died between 2007 and 2015. Multiple imputation was used to manage missing data, and generalised linear models were used to assess multiple adjusted associations between sociodemographic and clinical explanatory variables and acute service use at the end of life and in-hospital deaths. Results: A cohort of 1350 adults was analysed. More than half visited the accident and emergency (A&E) department in the last 90 days of life, and a third had a burdensome transition (multiple hospital admissions in the last 90 days of life or at least one in the last three days); the median number of days spent in the hospital was 4 (range: 0–86). Having more comorbidities was a strong correlate of more A&E visits (adjusted odds ratio [OR] = 1.03 [95% confidence interval = 1.02–1.04]), burdensome transitions (adjusted OR = 1.06 [1.04–1.08]) and days spent in the hospital (adjusted OR = 1.04 [1.03–1.05]). Having a diagnosis of schizophrenia spectrum disorder, compared with other serious mental disorder diagnoses, was associated with fewer A&E visits (adjusted OR = 0.78 [0.71–0.88]) and fewer days in the hospital (adjusted OR = 0.77 [0.66–0.89]). Younger age was associated with more A&E visits (adjusted OR = 1.28 [1.07–1.53]) and fewer days spent in the hospital (adjusted OR = 0.70 [0.52–0.95]). Hospital deaths were high (51%), and in a fully adjusted model, they were associated with having more comorbidities (adjusted OR = 1.02 [1.01–1.03]) and accessing acute care at the end of life (including more A&E visits; adjusted OR = 1.07 [1.05–1.10]), burdensome transitions (adjusted OR = 1.53 [1.37–1.71]) and days spent in the hospital (adjusted OR = 2.05 [1.70–247]). Conclusion: People with comorbidities are more likely to use more burdensome acute health care at the end of life and are more likely to die in the hospital. Hospital deaths could be reduced, and end-of-life care could be improved by targeting patients with comorbidities and who are accessing more acute healthcare services.